PENGARUH MODEL PEMBELAJARAN ROLE PLAYING TERHADAP PRESTASI BELAJAR BAHASA INDONESIA SISWA KELAS IV SDN LIWUNG KABUPATEN LOMBOK TENGAH NTB - Rahmatin, Laili Alfi (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2021)
The purpose of this study was to determine the effect of role playing learning models on student learning outcomes in Indonesian 8 Theme areas where I live in fiction stories grade 4 SDN Liwung Lobok Tengah. This research using is quantitative research using quasi experimental research designs. The sample used in this study is nonprability sampling with saturated sampling so that all student used as sample, all classes 4 consisting classes A and B. Class A was chosen as the control class dan class B was chosen as the experimental class, each class containing 25 student. The research instrument used was a test (pretest and posttest)a. The result of data analysis obtained from the independent t test are sig (2 tailed = 0,000) < ɑ 0, 05) it means that Ho is rejected dan Hɑ is accepted, Role Playing learing model affect student achievement.